Komunikasi Lingkungan Belajar Kontekstual Untuk Menguatkan Pemahaman Aplikatif Ilmu Agama Di Kalangan Santri - Miftahuddin Miftahuddin (Jurnal Komunikasi dan Media, 2024)
The learning environment plays a central role in shaping students’ character and religious understanding in Islamic boarding schools (pesantren). However, most previous studies have primarily focused on curriculum and teaching methods, leaving the dimension of contextual communication largely unexplored. This article aims to examine the role of contextual learning communication in strengthening the applied understanding of religious knowledge among santri. This research adopts a library research approach by reviewing relevant literature, journals, and academic works related to educational communication, pesantren, and religious value internalization. The data were analyzed descriptively and analytically to identify the patterns, functions, and contributions of contextual communication in pesantren education. The findings reveal that dialogical, participatory, and context-based communication effectively bridges the gap between religious theory and practical life. Effective communication enhances not only cognitive understanding but also reflective moral and spiritual awareness. The study concludes that strengthening contextual communication within the pesantren learning environment is a strategic step in developing a more humanistic, adaptive, and contextual Islamic education model. This article contributes to Islamic education discourse by positioning communication as a transformative tool for value internalization and the development of a religiously grounded character.